Potret Perempuan dalam Bingkai Ketatanegaraan - Nasution, Latipah ('ADALAH, 2019)
AbstractThe role of women is an absolute prerequisite for the realization of equitable development. The state will not be prosperous if the women are left behind, marginalized and oppressed. Efforts to empower women are an integral part of national development efforts. Therefore, women's empowerment is an ongoing effort to adjust to the times. The presence of various rules regarding women's representation in various aspects is a form of respect for women for the realization of a prosperous and just state.Keywords: Women, Political Participation, Rule of Law.Â Abstrak Peran perempuan merupakan syarat mutlak demi terwujudnya pembangunan yang berkeadilan. Negara tidak akan sejahtera apabila kaum perempuannya dibiarkan tertingal, tersisish dan tertindas. Upaya pemberdayaan perempuan merupakan bagian integral dari upaya pembangunan nasional. Oleh karena itu pemberdayaan perempuan merupakan upaya yang berkelanjutan menyesuaikan dengan perkembangan zaman. Hadirnya berbagai aturan mengenai representatif perempuan di berbagai aspek merupakan bentuk penghormatan terhadap perempuan demi terwujudnya negara yang sejahtera dan berkeadilan.Kata Kunci: Â Perempuan, Partisipasi Politik, Negara Hukum.